PERANAN KREDIT SIMPAN PINJAM TERHADAP PENINGKATAN USAHA ANGGOTA KOPERASI SIMPAN PINJAM (KSP) MOJOPAHIT JAYA DI DESA SARI GALUH KECAMATAN TAPUNG KABUPATEN KAMPAR - Indah Permata Sari; Cepriadi '; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims at knowing the role of business members before and after receiving credit from KSP Mojopahit Jaya. This study was conducted in Mojopahit Jaya saving and loan cooverative in Sari Galuh village Tapung district Kampar regency. The population in this study was the members who receive credit in the period January to April 2012, using a credit to productive enterprise. The sampling method conducted a census to 18 members.The result showed that business credit proved are able to raise the capital and asset. So that members operating revenues increased after the capital increase of the KSP Mojopahit Jaya,  where the average income of the business members before obtaining credit is Rp. 19.296.861 and after optaining credit increase to Rp. 23.547.349.   Key words : Credit, KSP, Income